(untitled) (Research, Society and Development, 2023)
The Zika virus infection, whose autochthonous transmission was recorded back in 2015 in Brazil, can be diagnosed during the gestational period and cause maternal-fetal complications. The present descriptive and cross-sectional study consists on analyzing the prevalence of pregnant women diagnosed with Zika in the state of Goiás during the period from 2015 to 2021, based on online data from the platform Tabnet/DATASUS. Data were tabulated in the Excel® program. Statistical analyzes were performed by calculating frequency using the Epi Info program version 2.0 The total number of notifications of suspected cases of Zika in pregnant women during the study period was 613 cases, with 142 laboratory confirmed cases (23.1%), with the highest prevalence being 20-24 years old (28%) and the most prevalent self-reported color/race being brown (57%). Regarding symptoms, the most prevalent symptom was fever (22.5%) and the most prevalent sign was exanthema (48.5%). Regarding newborns whose mothers were laboratory-diagnosed with Zika during pregnancy, there were 43 (30%) laboratory-confirmed cases of Zika. The analysis of the sociodemographic profile of pregnant women diagnosed with Zika virus during prenatal care allows to better identify and analyze possible risk factors for infection and, therefore, public health measures can be specifically implemented for this group.